40 MICROARRAY ANALYSIS OF HEPATIC GENE EXPRESSION IN OBESE HUMANS UNDERGOING BARIATRIC SURGERY. (1st January 2006) - Gandhi, M.; Elam, M. B.; Cowan, G. S.; Bahr, M.; Hiler, M. L.; Cagen, L.; Deng, X.; Yellaturu, C.; Wilcox, H.; Patel, D.; Allan, C.; Wodi, L.
Abstract : Obesity is consistently accompanied by the development of resistance to the effect of insulin to promote glucose uptake in skeletal muscle. The resulting glucose intolerance leads to development of hyperinsulinemia, which, in turn, promotes synthesis of lipid by the liver (de novo lipogenesis and triglyceride synthesis). This leads to overproduction of VLDL and elevated levels of triglyceride-rich lipoproteins in the plasma. Excess lipid also accumulates in the liver to produce fatty liver (hepatic steatosis). Although these processes have been well characterized in animal models of obesity and hyperinsulinemia, little information is available regarding these processes in livers of obese humans. To gain insight into the pathophysiology of hepatic lipid production in obese humans we examined global gene expression using Affymetrix human HG-U133A microarray chip in liver biopsy samples obtained from obese patients who were undergoing gastric-bypass surgery for weight loss and from post-obese individuals who were undergoing abdominal wall revision (tummy tuck) after weight loss following prior gastric-bypass surgery. Of the 22, 400 probe sets on the chip 3, 576 genes were expressed at a 95% or greater level of detection certainty. From this dataset 39 genes were identified that were highly overexpressed (2-fold or greater) in obese livers, and 33 genes were identified that were underexpressed (22-fold or greater) in obese livers as compared to post-obese controls. Functional analysis of over- and underexpressed genes revealed altered expression of genes related to insulin signaling, lipid metabolism, inflammation, proliferation, and immunologic response. Several genes of specific interest for insulin resistance and hepatic lipid synthesis were highly regulated in obese human liver. These include genes related to insulin signaling [suppressor of cytokine signaling 2 (SOCS2) and leptin receptor (LEP)], inflammation [C-reactive protein (CRP) and superoxide dismutase (SOD2)], and lipid synthesis [fatty acid synthase (FASN)]. The potential significance of altered expression of these and other genes in obese human liver is discussed.